THE MAKING OF TIN AND RUBBER BALL GAME TO LEARN ENGLISH VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Yuni Safitri; Rionaldi Rionaldi (Politeknik Negeri Bengkalis, 2018)
Mastering English is very important for everyone around the world. By mastering English, everyone can communicate well and do all things related to English. However, learning using medium will surely help to understand the lesson well, and then they can learn English in a more effective and interesting way. The main purpose of this final project is to make Tin and Rubber Ball Game to learn English vocabulary for Elementary school students. The method used for this study is descriptive research. There were several processes taken to complete this game and the final project, started from collecting the materials, designing processes, and making the game. The result of this study was a set of tin game, consisting of eight tins consisting of eight topics, two rubbers and ten cards about the topics in each of tin. By using this game, students can learn and improve their English vocabulary.